2013
DOI: 10.1111/ene.12180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blood pressure changes and course on hematoma growth in acute intracerebral hemorrhage

Abstract: In patients with acute supratentorial ICH, SBP 180-load independently predicts HG, whilst both SBP 180-load and SBP variability predict END.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 24 publications
2
116
2
9
Order By: Relevance
“…6,7 The similarities of the findings between the study by Rodriguez-Luna et al 6 and the present one were that SBP variability was predictive of early neurological deterioration but not predictive of hematoma expansion.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…6,7 The similarities of the findings between the study by Rodriguez-Luna et al 6 and the present one were that SBP variability was predictive of early neurological deterioration but not predictive of hematoma expansion.…”
Section: Discussionsupporting
confidence: 74%
“…However, ours showed the positive association between SBP variability and absolute and relative changes in hematoma volume. Differences between the study by Rodriguez-Luna et al 6 and the present one were the baseline SBP level (mean, 172 versus 200 mm Hg), the proportion of patients receiving emergent AHT (43.6% versus 100%), and that the present one assessed the association of SBP variability with 3-month clinical outcomes, which was found to be significant. In the present study, not only vital outcome but also functional outcomes were assessed.…”
Section: The Similarities Between the Interact2contrasting
confidence: 69%
“…Elevated blood pressure has been shown to be associated with the risk of hematoma expansion in patients with spontaneous intracerebral hemorrhage. [115][116][117] In patients with spontaneous intracerebral hemorrhage, studies showed the relative safety of intensive systolic blood pressure lowering to a goal of <140 mm Hg, e354…”
Section: -114mentioning
confidence: 99%
“…Mean SBP levels were significantly different between randomized groups from 15 minutes to day 7 post randomization; 150 mm Hg in the intensive group (462 [33%] achieved the target SBP) compared with 164 mm Hg in the guideline group (difference, 14 mm Hg; P<0.001) at 1 hour. Mean (SD)-achieved SBPs in the 1-to 24-hour and 2-to 7-day periods were 142 (13) mm Hg and 155 (14) mm Hg and 140 (11) mm Hg and 149 (13) mm Hg, in the intensive and guideline groups, respectively. 21 The primary outcome was death or major disability defined by the modified Rankin Scale (mRS), 22 and the secondary outcome was physical function across all 7 levels in an ordinal shift analysis of the mRS, 23 at 90 days post randomization.…”
Section: Methodsmentioning
confidence: 96%
“…Some studies have implied adverse effects from reducing systolic BP (SBP), [8][9][10] whereas others have indicated clinical improvement with higher SBP reduction [11][12][13][14] or no benefits at all of such treatment in ICH. 15 An important meta-regression analysis of randomized controlled trials of altered BP in acute stroke showed a J-shaped relationship, with the best outcomes from modest SBP reduction (<10 mm Hg), but the number of patients included with ICH was limited.…”
mentioning
confidence: 99%